The Sound of Innovation : Stanford and the Computer Music Revolution - Nelson, Andrew J. (Book collections on Project MUSE., 2015)
How a team of musicians, engineers, computer scientists, and psychologists developed computer music as an academic field and ushered in the era of digital music.